Firm Investment, Liquidity, and Bank Health: A Panel Study of Asian Firms in the 2000s - Kazuo Ogawa (Asian Development Bank (ADB), 2013)
The purpose of this study is to investigate how firms responded to the deterioration of bank health during the financially turbulent periods in the 2000s in making investment decisions and in meeting demand for liquidity. A rise in uncertainty regarding the ability to obtain external funds may have induced firms to rely on internal funds to finance investment activities. Therefore, we shed light on the cash flow sensitivity of investment and cash holdings by estimating firm- level investment and cash holdings equations using panel data for Asian firms in the 2000s. Our sample firms are from countries at different stages of financial development. The sample enables us to analyze the different roles played by internal funds in the financial and investment policy of firms in a financial environment with different stages of development. We find that the cash flow sensitivity of investment and cash holdings rises as bank health deteriorates. Moreover, the impact of non-performing loans on the cash flow sensitivity of investment and cash holdings is more prevalent across firms, irrespective of firm age, in countries with a higher level of financial intermediary development. Our findings suggest that as financial intermediaries develop, firms become more dependent on bank credit so that bank-dependent firms are more vulnerable to external shocks that hit the financial system. Therefore, when bank health is impaired, bank-dependent firms increase their reliance on internal funds and raise their propensity to save cash flow to materialize potentially profitable investment opportunities in the future.
hdl:11540/2088
Keywords: E21; E22; E44; G31; G32; O16; 330; nvestment; financial constraint; cash flow sensitivity; cash holdings; bank health; Bankenkrise; Bankenliquidität; Kreditgeschäft; Investition; Unternehmensfinanzierung; Asien